Artificial Intelligence in English Language Teaching: A Study of English Teachers' TPACK - Sabaruddin Sabaruddin; Atmaranie Dewi Purnama; Harmilawati Harmilawati; Sitti Aminah; Irmayani Irmayani; Takdir Takdir; Amran AR (Globish: An English-Indonesian Journal for English, Education, and Culture, 2024)
The use of AI in language education has been widely discussed especially in identifying the teachers’ ability in utilizing AI in language teaching as well as how teachers perceive the utilization of AI are significant. To address these needs, the researchers used a TPACK survey instrument and semi-structured interview to assess 6 English teachers' ability to use AIEd at Islamic University of Ahmad Dahlan. Findings show that there are several challenges faced by the users of AIEd in English language courses such as (1) limited technological knowledge, (2) lack of training, (3) limited access to technological resources, (4) student skill levels, (5) policy and administrative constraints, as well as (6) curriculum changes and needs. Overall, the application of AIEd in language teaching in UIAD has the potential to significantly enhance learning outcomes for English learners by providing personalized, adaptive, and engaging learning experiences supported by data-driven insights and continuous improvement.